« Si cet homme n’avait pas été prêtre… » - Constance Lalo (Association Paul Langevin, 2020)
Since the 1980s, cases of sexual violence have received increasing media attention in the West. This media coverage focused on pedocriminality within the Catholic Church. Does such media framing imply a specificity of the Church in this kind of cases? Is the Church a singularly violent patriarchal institution, or is it just one manifestation among others, within a social continuum, of the patriarchy of power? While it seems impossible today to answer this question with certainty, this article shows that two unthought-out elements of the Catholic “script” play a major role in the resistance of Catholics to denounce and manage the pedocriminal practices of priests in favour of the protection and reparation of victims: the difficulty of considering the possibility of abuse of power, the latter being conceived as a service; and the difficulty of seeing sexual consent as the nodal point of all sexual activity, regardless of the "quality" of the partners involved and the harm done to the institution when one of its clerics is involved.